2015
DOI: 10.1002/ajmg.a.37097
|View full text |Cite
|
Sign up to set email alerts
|

A familial interstitial 4q35 deletion with no discernible clinical effects

Abstract: Small deletions on the long arm of distal chromosome 4 do not appear to result in gross congenital malformations, with the most frequently reported clinical findings including mild to moderate intellectual disability, learning disabilities and minor dysmorphic features. Here we report on a cytogenetically detectable familial interstitial chromosome 4 long arm deletion with no discernible phenotypic effects in a mother and her two daughters. The karyotypes of the mother and her two daughters were: 46,XX,del(4)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Also, while their case had a heterozygous deletion of 4q35.2, they believe that the clinical manifestations of the case were due to the duplication of the chromosome 2q34 region. Strikingly, in the family described by Yakut et al [2015], no clinical effect was observed in either the mother or her 2 daughters, even though they each had a 5.75-Mb deletion in the chromosome 4q35.1q35.2 region. Based on the findings of these 2 publications and our case, it appears that the chromosome 4q35.2 region can be polymorphic.…”
Section: Discussionmentioning
confidence: 88%
“…Also, while their case had a heterozygous deletion of 4q35.2, they believe that the clinical manifestations of the case were due to the duplication of the chromosome 2q34 region. Strikingly, in the family described by Yakut et al [2015], no clinical effect was observed in either the mother or her 2 daughters, even though they each had a 5.75-Mb deletion in the chromosome 4q35.1q35.2 region. Based on the findings of these 2 publications and our case, it appears that the chromosome 4q35.2 region can be polymorphic.…”
Section: Discussionmentioning
confidence: 88%
“…In order to establish a genotype-phenotype correlation, the severity of the phenotype is correlated with the size of the deletion. Thus, several reports suggested that small terminal, or interstitial, distal Cr4q del involving bands 4q34 and 4q35 seems to have little clinical impact, consisting in little facial dysmorphism and mild, or absent, intellectual disability (ID) 4 , and Yakut et al 5 reported a case of a familial interstitial 4q35 deletion with no discernible phenotypic effects. On the other hand, a relatively constant phenotype can be recognised in 4q31 to qter deletion.…”
Section: Introductionmentioning
confidence: 99%
“…Alhamoudi et al 2020), vgll4(Czeschik et al 2014)(Barrionuevo et al 2014), and vwa1(Giannikou et al 2012). Among the downregulated genes we also found the following candidates to have such roles; acsl1(Yakut et al 2015), adgb(Alazami et al Miller et al 2009), hoxa13(Fryssira et al 2011), il23r (Rivera-Pedroza et al. 2017, ppp1r42(Mordaunt et al 2015), prodh(Guilmatre et al 2010), six2(Hufnagel et al 2016)(Okello et al 2017), srsf3 (Pillai et al 2019, syt9(Sofos et al 2012), and trpc2 …”
mentioning
confidence: 78%